Production and Use of Veterinary Vaccines in Sudan - Hajer, I. E.; Hassan, A. M. (Journal of Veterinary Medicine and Animal Production, 2021)
This article aims at reviewing the production of veterinary vaccines used in the Sudan to control diseases of livestock and poultry. The paper covers the principals and a procedure employed in the production of live and inactivated viral and bacterial vaccines and specifically describes the production of ten viral vaccines used in Sudan including Rinderpest and Peste des Petite Ruminants (PPR), Rift Valley Fever, Lumpy Skin Disease, Sheep Pox, Blue Tongue, Camel Pox, African Horse (AHS), Newcastle Disease, Fowl Pox and Gumboro. It also describes the production of four bacterial vaccines; namely vaccines against Anthrax, Hemorrhagic Septicemia Black Quarter and Brucellosis, as well as vaccines against two Mycoplasma diseases, namely Contagious Bovine Pleuropneumonia and Contagious Caprine Pleuropneumonia. The paper concludes that, Sudan with its many strong and diversified facilities is qualified for vaccine production, to cover the need for control of all diseases in the OIE list of socioeconomic significance for the country and the region. These facilities include an animal wealth estimated to be 100 million tropical animal units (TAU), and an excellent geostrategic position as far as marketing of animals and animal products are concerned; together with Veterinary services and research institutions established since the turn of the 20th Century, and research facilities together with available trained an well experienced personnel. Modern and up-to-date research methodology is necessary for development of vaccine production techniques and generation of new and improved veterinary vaccines so that vaccine production laboratory in the Sudan becomes rated as a Regional Research Center and a Reference Laboratory for training of personnel and vaccine production in Africa and Arab countries. However, recent advances in bio-technology and information technology provide enormous promises and opportunities; however, political will, strategic planning adequate funding and proper training of the personnel are needed.